Modified polytetrafluoroethylene and stretched body

By introducing an appropriate amount of hexafluoropropylene unit into polytetrafluoroethylene and adopting a specific polymerization process, the problem of difficult to take into account both high fracture strength and low extrusion pressure in the prior art is solved, and efficient moldability and heat resistance are achieved.

CN119654356APending Publication Date: 2025-03-18DAIKIN INDUSTRIES LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380057984.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-10
Filing Date
2023-08-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to reduce the extrusion pressure of modified polytetrafluoroethylene while maintaining high fracture strength, affecting its moldability.

Method used

By introducing hexafluoropropylene units into polytetrafluoroethylene, adjusting their composition ratio so that the amount of hexafluoropropylene units is less than 1.0 mass% relative to all polymerization units, and combining a specific polymerization process, such as emulsion polymerization, a modified polytetrafluoroethylene with high fracture strength but low extrusion pressure is obtained.

Benefits of technology

It is achieved to significantly reduce the extrusion pressure while maintaining high fracture strength, and improve the moldability and heat resistance of modified polytetrafluoroethylene.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005262118530000211
    Figure BDA0005262118530000211
Patent Text Reader

Abstract

Provided are a modified polytetrafluoroethylene having a low extrusion pressure despite high breaking strength, and a stretched body using the same. A modified polytetrafluoroethylene containing tetrafluoroethylene units and hexafluoropropylene units, the amount of the hexafluoropropylene units being 1.0 mass% or less with respect to the total polymerization units, the breaking strength being 20.0 N or more, and the thermal instability index being less than 40.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to modified polytetrafluoroethylene and a stretched body. Background Art

[0002] When polytetrafluoroethylene is highly stretched in the molded and unfired state, a porous polytetrafluoroethylene membrane can be obtained. This porous membrane allows gases such as water vapor to pass through, but water droplets cannot pass through due to the strong water repellency of polytetrafluoroethylene. This unique property is used in clothing, separation membranes, etc.

[0003] Patent Document 1 describes polytetrafluoroethylene fine powder having units based on a comonomer such as CH2=CH-(CF2)4F.

[0004] Patent Document 2 describes a modified polytetrafluoroethylene fine powder having a unit based on perfluoro(methyl vinyl ether).

[0005] Patent Document 3 describes a tetrafluoroethylene homopolymer or a polytetrafluoroethylene powder having units based on hexafluoropropylene.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2011 / 055824

[0009] Patent Document 2: Japanese Patent Application Publication No. 2015-127411

[0010] Patent Document 3: International Publication No. 2020 / 022355 Summary of the invention

[0011] Technical problem to be solved by the invention

[0012] An object of the present invention is to provide a modified polytetrafluoroethylene having a low extrusion pressure despite high breaking strength, and a drawn product using the same.

[0013] Solutions to technical problems

[0014] The present invention (1) is a modified polytetrafluoroethylene comprising tetrafluoroethylene units and hexafluoropropylene units, wherein the amount of the hexafluoropropylene units is 1.0 mass % or less relative to the total polymer units, the breaking strength is 20.0 N or more, and the thermal instability index is less than 40.

[0015] The present invention (2) is the modified polytetrafluoroethylene according to the present invention (1), wherein the strength ratio represented by breaking strength (N) / extrusion pressure (MPa) is 1.80 N / MPa or more.

[0016] The present invention (3) is the modified polytetrafluoroethylene according to the present invention (1) or (2), wherein the stress relaxation time is 500 seconds or more.

[0017] The present invention (4) is a modified polytetrafluoroethylene in combination with any one of the present inventions (1) to (3), wherein the extrusion pressure is less than 17.0 MPa.

[0018] The present invention (5) is a modified polytetrafluoroethylene in combination with any one of the present inventions (1) to (4), wherein the extrusion pressure is less than 16.0 MPa.

[0019] The present invention (6) is a modified polytetrafluoroethylene comprising tetrafluoroethylene units and hexafluoropropylene units, wherein the amount of the hexafluoropropylene units is less than 0.1% by mass based on all polymerized units.

[0020] The present invention (7) is a modified polytetrafluoroethylene in combination with any one of the present inventions (1) to (6), which is in the form of a powder.

[0021] The present invention (8) is a modified polytetrafluoroethylene in combination with any one of the present inventions (1) to (7), which is in the form of a fine powder.

[0022] The present invention (9) is a stretched product formed of modified polytetrafluoroethylene in combination with any one of the present inventions (1) to (8).

[0023] Effects of the Invention

[0024] According to the present invention, it is possible to provide a modified polytetrafluoroethylene having a low extrusion pressure despite high breaking strength, and a stretched product using the same. DETAILED DESCRIPTION

[0025] Generally, when the extrusion pressure of polytetrafluoroethylene (PTFE) is increased, the breaking strength can be increased, but the paste extrudate becomes hard and the moldability of the extrudate tends to deteriorate.

[0026] However, as a result of intensive studies, it has been found that, in modified PTFE using hexafluoropropylene as a modifying monomer, by adjusting the composition of tetrafluoroethylene and hexafluoropropylene during polymerization to a specific range, PTFE having a low extrusion pressure despite high breaking strength can be obtained, contrary to common technical knowledge.

[0027] The present invention is described in detail below.

[0028] The present invention provides a modified PTFE (hereinafter also referred to as the first modified PTFE), which contains tetrafluoroethylene (TFE) units and hexafluoropropylene (HFP) units, wherein the amount of the HFP units is 1.0 mass% or less relative to all polymerized units, has a breaking strength of 20.0N or more, and has a thermal instability index of less than 40.

[0029] The first modified PTFE has the above-mentioned structure, and thus has a low extrusion pressure and excellent moldability despite its high breaking strength. The reason is still unclear, but it is speculated that HFP exists in the reaction system before the polymerization is completed due to the low reactivity of HFP and TFE, which affects the physical properties of the obtained modified PTFE.

[0030] In addition, the first modified PTFE is also excellent in heat resistance.

[0031] The first modified PTFE contains TFE units (polymerized units based on TFE) and HFP units (polymerized units based on HFP), and the amount of the HFP units is 1.0% by mass or less based on all the polymerized units.

[0032] The content of the TFE unit in the modified PTFE may be 99.0% by mass or more.

[0033] The modified PTFE may further include polymerized units based on modifying monomers other than TFE and HFP (other modifying monomer units).

[0034] As the above-mentioned other modifying monomers, there is no particular limitation as long as they can be copolymerized with TFE, and examples thereof include hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF]; perhaloolefins such as chlorotrifluoroethylene; perfluoroolefins; perfluorovinyl ether; perfluoroallyl ether; (perfluoroalkyl)ethylene, ethylene, etc. In addition, the above-mentioned other modifying monomers used may be one or more.

[0035] The content of the other modified monomer units is preferably less than 1.0% by mass, more preferably 0.1% by mass or less, based on the total polymerized units.

[0036] The total amount of the HFP unit and the other modified monomer units is preferably 1.0% by mass or less based on the total polymerized units.

[0037] The content of the HFP unit is 1.0% by mass or less relative to the total polymerized units. From the viewpoint of further reducing the extrusion pressure and further improving the breaking strength, the content of the HFP unit is preferably 0.50% by mass or less, more preferably 0.30% by mass or less, further preferably 0.10% by mass or less, still more preferably 0.05% by mass or less, particularly preferably 0.02% by mass or less, and particularly preferably 0.01% by mass or less relative to the total polymerized units.

[0038] The content of the HFP unit may be 0.0001% by mass or more, or 0.001% by mass or more, based on the total polymerized units.

[0039] In this specification, the HFP unit refers to a part of the molecular structure of modified PTFE and is a part derived from HFP.

[0040] The content of each polymerized unit described above can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and fluorescent X-ray analysis according to the type of monomer.

[0041] The breaking strength of the first modified PTFE is 20.0 N or more. The breaking strength is preferably 25.0 N or more, more preferably 28.0 N or more, and further preferably 30.0 N or more. The higher the breaking strength, the better, and it may be 100.0 N or less, 80.0 N or less, or 50.0 N or less.

[0042] The above-mentioned breaking strength is a value obtained by the following method.

[0043] The tensile bar (made by stretching a bar) obtained in the following tensile test performed at a tensile speed of 100% / sec was clamped and fixed in a movable jaw with a gauge length of 5.0 cm, and a tensile test was performed at 25°C at a speed of 300 mm / min, and the strength at break was measured as the breaking strength.

[0044] The thermal instability index (TII) of the first modified PTFE is less than 40. The thermal instability index is preferably 15 or less, more preferably 10 or less, and particularly preferably less than 5, from the viewpoints of lower extrusion pressure, higher breaking strength, and further improved heat resistance.

[0045] The thermal instability index is preferably -10 or greater, more preferably 0 or greater.

[0046] The thermal instability index is measured in accordance with ASTM D 4895.

[0047] The extrusion pressure of the first modified PTFE is preferably 20.0 MPa or less, more preferably less than 18.0 MPa, further preferably less than 17.0 MPa, and still more preferably less than 16.0 MPa. The extrusion pressure may be 5.0 MPa or more, or 10.0 MPa or more.

[0048] The extrusion pressure is a value obtained by the following method.

[0049] 21.7 g of lubricant (trade name: Isopar H (registered trademark), manufactured by Exxon) was added to 100 g of modified PTFE powder, and mixed at room temperature for 3 minutes to obtain a PTFE fine powder mixture. Next, the obtained PTFE fine powder mixture was placed at room temperature (25°C) for at least 1 hour before extrusion, and then paste extruded through a hole (diameter 2.5 mm, land length 11 mm, introduction angle 30°) at room temperature with a reduction ratio of 100:1 (ratio of the cross-sectional area of ​​the inlet of the die to the cross-sectional area of ​​the outlet) to obtain a uniform beading (extruded molded body). The extrusion speed, i.e., the punch speed, was set to 20 inches / minute (51 cm / minute). The extrusion pressure is a value obtained by measuring the load when the extrusion load reaches a balanced state in the paste extrusion and dividing it by the cross-sectional area of ​​the barrel used in the paste extrusion.

[0050] The strength ratio of the first modified PTFE represented by the breaking strength (N) / extrusion pressure (MPa) is preferably 1.80 N / MPa or more, more preferably 1.85 N / MPa or more, further preferably 1.90 N / MPa or more, further preferably 1.95 N / MPa or more, further more preferably 2.00 N / MPa or more. The higher the strength ratio, the better, and it can be 5.00 N / MPa or less, 4.00 N / MPa or less, or 3.00 N / MPa or less.

[0051] A higher strength ratio means a higher breaking strength and a lower extrusion pressure.

[0052] The above-mentioned breaking strength and extrusion pressure are values ​​obtained by the above-mentioned method.

[0053] The first modified PTFE is preferably stretchable. In this specification, "stretchable" is determined by the following criteria.

[0054] The strips obtained by extruding the above paste are dried at 230°C for 30 minutes, and the lubricant is removed from the strips. Next, the strips (extruded molded bodies) are cut into appropriate lengths, and each end is fixed to the chucks in a manner that the chuck spacing is 2.0 inches (51 mm), and heated to 300°C in an air circulation oven. Next, the chucks are separated at the desired speed (stretching speed) to a separation distance equivalent to the desired stretching (total stretching), and a stretching test is performed. This stretching method is essentially in accordance with the method disclosed in the specification of U.S. Patent No. 4,576,869, except that the extrusion speed (51 cm / minute instead of 84 cm / minute) is different. "Stretching" refers to the increase in length caused by extension, and is usually expressed in relation to the original length. In the above-mentioned production method, the above-mentioned stretching speed is 1000% / second, and the above-mentioned total stretching is 2400%. The situation in which there is no breakage until the above-mentioned stretching is completed is judged to be able to stretch.

[0055] The modified PTFE of the present invention is preferably not broken even after the stretching is completed when a stretching test is conducted under the conditions of a stretching speed of 100% / sec and a total stretching of 2400% in the above-mentioned production method.

[0056] From the viewpoint of further improving heat resistance, the stress relaxation time of the first modified PTFE is preferably 500 seconds or more, more preferably 550 seconds or more, further preferably 600 seconds or more, and particularly preferably 650 seconds or more.

[0057] The longer the stress relaxation time is, the better, and it may be 2000 seconds or less, or 1000 seconds or less.

[0058] The above-mentioned stress relaxation time is a value obtained by the following method.

[0059] The two ends of the tensile strip obtained in the same manner as the above tensile evaluation test performed at a tensile speed of 1000% / sec were connected to a fixture to prepare a tensed strip sample with a total length of 8 inches (20 cm). The oven was maintained at 390°C, and the fixture was inserted into the oven through a slit located in the side of the oven (covered). The time required from the time of insertion into the oven to the breakage of the strip sample was measured as the stress relaxation time.

[0060] From the perspective of excellent stretchability, the standard specific gravity (SSG) of the first modified PTFE is preferably 2.200 or less, more preferably 2.180 or less, further preferably 2.170 or less, still more preferably 2.160 or less, particularly preferably 2.155 or less, and particularly preferably 2.150 or less.

[0061] In addition, the standard specific gravity is preferably 2.130 or more.

[0062] The standard specific gravity is measured by a water displacement method according to ASTM D 792 using a sample molded according to ASTM D 4895.

[0063] The first modified PTFE generally has non-melt secondary processability. The non-melt secondary processability refers to the property that the melt flow rate cannot be measured at a temperature higher than the melting point according to ASTM D-1238 and D-2116, in other words, the property that it is not easy to flow even in the melting temperature range.

[0064] The first modified PTFE can have a core-shell structure. As the PTFE with a core-shell structure, for example, a modified PTFE comprising a core of a high molecular weight PTFE and a shell of a lower molecular weight PTFE or modified PTFE in a particle can be enumerated. As such a modified PTFE, for example, the PTFE recorded in writing in the Japanese special public clear 65-8022 communique can be enumerated.

[0065] The first modified PTFE can be produced, for example, by a production method including the step of emulsion polymerizing TFE and HFP (and other modifying monomers as necessary).

[0066] The above-mentioned emulsion polymerization can be carried out in an aqueous medium in the presence of an anionic fluorinated surfactant and a polymerization initiator, for example.

[0067] The emulsion polymerization can be carried out as follows: an aqueous medium, the anionic fluorinated surfactant, a monomer and other additives as needed are added to a polymerization reactor, the contents of the reactor are stirred, the reactor is maintained at a specified polymerization temperature, and then a specified amount of a polymerization initiator is added to initiate the polymerization reaction. After the polymerization reaction starts, monomers, polymerization initiators, chain transfer agents and the surfactants can be added according to the purpose. Surfactants can also be added after the polymerization reaction starts.

[0068] As the above-mentioned polymerization initiator, there is no particular limitation as long as it can generate free radicals in the polymerization temperature range, and known oil-soluble and / or water-soluble polymerization initiators can be used. Furthermore, it is also possible to combine with a reducing agent etc. to initiate polymerization in a redox form. The concentration of the above-mentioned polymerization initiator is appropriately determined according to the type of monomer, the molecular weight of the target modified PTFE, and the reaction rate.

[0069] As the polymerization initiator, an oil-soluble radical polymerization initiator or a water-soluble radical polymerization initiator can be used.

[0070] The oil-soluble free radical polymerization initiator may be a known oil-soluble peroxide, and for example, the following peroxides may be cited as representative substances: dialkyl peroxycarbonates such as diisopropyl peroxydicarbonate and di-sec-butyl peroxydicarbonate; peroxyesters such as tert-butyl peroxyisobutyrate and tert-butyl peroxypivalate; dialkyl peroxides such as di-tert-butyl peroxide; and di(ω-hydro-dodecafluoroheptanoyl) peroxide, di(ω-hydro-tetradecafluoroheptanoyl) peroxide, di(ω-hydro-hexadecanoyl) peroxide, di(perfluorobutanoyl) peroxide, di(perfluoropentanoyl) peroxide, di(perfluorohexanoyl) peroxide, di(perfluoroheptanoyl) peroxide, di(perfluorooctanoyl) peroxide. peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl)peroxide, di(ω-chloro-decafluorohexanoyl)peroxide, di(ω-chloro-tetrafluorooctanoyl)peroxide, ω-hydro-dodecafluoroheptanoyl-ω-hydrohexafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydro-dodecafluoroheptanoyl-perfluorobutyryl-peroxide, di(dichloropentafluorobutyryl)peroxide, di(trichlorooctafluorohexanoyl)peroxide, di(tetrachloroundecanoyl)peroxide, di(pentachlorotetrafluorodecanoyl)peroxide, di(undecanotridodecanoyl)peroxide and the like di[perfluoro(or fluorochloro)acyl]peroxides; and the like.

[0071] As the water-soluble free radical polymerization initiator, it can be a known water-soluble peroxide, for example, ammonium salts, potassium salts, sodium salts of persulfuric acid, perboric acid, perchloric acid, perphosphoric acid, percarbonic acid, tert-butyl peroxymaleate, tert-butyl hydroperoxide, etc. It can also contain a reducing agent such as sulfites and sulfites, and its amount can be 0.1 to 20 times that of the peroxide.

[0072] The amount of the water-soluble free radical polymerization initiator added is not particularly limited, and may be added once, sequentially, or continuously at the initial stage of polymerization in an amount that does not significantly reduce the polymerization rate (e.g., a concentration of several ppm relative to water). The upper limit is a range in which the heat of the polymerization reaction can be used to remove heat from the device surface and the reaction temperature can be increased, and a more preferred upper limit is a range in which the heat of the polymerization reaction can be removed from the device surface.

[0073] From the perspective of easily obtaining the above-mentioned physical properties, especially excellent tensile properties, the amount of polymerization initiator added is preferably an amount equivalent to 0.1 ppm or more, more preferably an amount equivalent to 1.0 ppm or more, relative to the aqueous medium. In addition, it is preferably an amount equivalent to 100 ppm or less, and more preferably an amount equivalent to 10 ppm or less.

[0074] For example, when the polymerization is carried out at a low temperature below 30°C, it is preferred to use a redox initiator that combines an oxidant and a reductant as a polymerization initiator. As the oxidant, persulfates, organic peroxides, potassium permanganate, manganese triacetate, ammonium cerium nitrate, bromates, etc. can be mentioned. As the reductant, sulfites, bisulfites, bromates, diimides, oxalic acid, etc. can be mentioned. As persulfates, ammonium persulfate and potassium persulfate can be mentioned. As sulfites, sodium sulfite and ammonium sulfite can be mentioned. In order to increase the decomposition rate of the initiator, it is also preferred to add copper salts and iron salts to the combination of redox initiators. As copper salts, copper (II) sulfate can be mentioned, and as iron salts, iron (II) sulfate can be mentioned.

[0075] As the redox initiator, it is preferred that the oxidizing agent is permanganic acid or a salt thereof, persulfate, manganese triacetate, cerium (IV) salt, or bromic acid or a salt thereof, and the reducing agent is dicarboxylic acid or a salt thereof, or diimine.

[0076] More preferably, the oxidizing agent is permanganic acid or a salt thereof, persulfate, or bromic acid or a salt thereof, and the reducing agent is a dicarboxylic acid or a salt thereof.

[0077] Examples of the redox initiator include combinations of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, manganese triacetate / oxalic acid, manganese triacetate / ammonium oxalate, cerium ammonium nitrate / oxalic acid, and cerium ammonium nitrate / ammonium oxalate.

[0078] When a redox initiator is used, either the oxidant or the reductant may be placed in a polymerization vessel in advance, and then the other may be added continuously or intermittently to initiate polymerization. For example, when potassium permanganate / ammonium oxalate is used, it is preferred that ammonium oxalate is placed in the polymerization vessel and potassium permanganate is continuously added thereto.

[0079] It should be noted that, in the redox initiator of the present specification, when "potassium permanganate / ammonium oxalate" is described, it means a combination of potassium permanganate and ammonium oxalate. The same applies to other compounds.

[0080] The redox initiator is particularly preferably a combination of an oxidizing agent which is a salt and a reducing agent which is a salt.

[0081] For example, the oxidizing agent as the salt is more preferably at least one selected from the group consisting of persulfate, permanganate, cerium (IV) salt and bromate, further preferably permanganate, and particularly preferably potassium permanganate.

[0082] The reducing agent for the salt is more preferably at least one selected from the group consisting of oxalates, malonates, succinates, glutarates and bromates, further preferably oxalates, and particularly preferably ammonium oxalate.

[0083] Specifically, the redox initiator is preferably at least one selected from the group consisting of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, potassium bromate / ammonium sulfite, manganese triacetate / ammonium oxalate and cerium ammonium nitrate / ammonium oxalate, more preferably at least one selected from the group consisting of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, potassium bromate / ammonium sulfite and cerium ammonium nitrate / ammonium oxalate, and further preferably potassium permanganate / oxalic acid.

[0084] When a redox initiator is used, the oxidant and the reducing agent may be added at once at the beginning of the polymerization, the reducing agent may be added at once and the oxidant may be added continuously at the beginning of the polymerization, the oxidant may be added at once and the reducing agent may be added continuously at the beginning of the polymerization, or both the oxidant and the reducing agent may be added continuously.

[0085] When one of the redox polymerization initiators is added at the initial stage of polymerization and the remaining one is added continuously, it is preferred to gradually reduce the rate of addition from the perspective of obtaining PTFE with low SSG, and it is further preferred to stop the addition during the polymerization. As the timing for stopping the addition, it is preferred to stop before 20 to 40% by mass of all TFE consumed in the polymerization reaction is consumed.

[0086] When a redox initiator is used as a polymerization initiator, the amount of the oxidant added is preferably 0.1 ppm or more, more preferably 1.0 ppm or more, further preferably 5 ppm or more, further more preferably 10 ppm or more, and preferably 10000 ppm or less, and more preferably 1000 ppm or less, relative to the aqueous medium. The amount of the reducing agent added is preferably 0.1 ppm or more, more preferably 1.0 ppm or more, further preferably 5 ppm or more, further more preferably 10 ppm or more, and preferably 10000 ppm or less, and more preferably 1000 ppm or less.

[0087] When a redox initiator is used in the emulsion polymerization, the polymerization temperature is preferably 100°C or lower, more preferably 95°C or lower, and further preferably 90°C or lower. It is preferably 10°C or higher, more preferably 20°C or higher, and further preferably 30°C or higher.

[0088] From the viewpoint of easily obtaining the above-mentioned physical properties, the polymerization initiator is preferably a water-soluble radical polymerization initiator or a redox initiator.

[0089] The aqueous medium is a reaction medium for polymerization and is a liquid containing water. The aqueous medium is not particularly limited as long as it contains water, and may contain water and a non-fluorinated organic solvent such as alcohol, ether, or ketone and / or a fluorinated organic solvent having a boiling point of 40° C. or less.

[0090] In the emulsion polymerization, a nucleating agent, a chain transfer agent, a buffer, a pH adjuster, a stabilizing aid, a dispersion stabilizer, a radical scavenger, a decomposing agent of a polymerization initiator, and the like may be used as necessary.

[0091] From the viewpoint of easily obtaining the above-mentioned various physical properties, the above-mentioned emulsion polymerization is preferably carried out by adding a nucleating agent. The above-mentioned nucleating agent is preferably added before starting the polymerization reaction.

[0092] As the nucleating agent, a known nucleating agent can be used, and for example, at least one selected from the group consisting of fluoropolyethers, nonionic surfactants, and chain transfer agents is preferred, and a nonionic surfactant is more preferred.

[0093] Examples of the fluorinated polyether include perfluoropolyether (PFPE) acid and salts thereof.

[0094] The above-mentioned perfluoropolyether (PFPE) acid or its salt may have any chain structure in which oxygen atoms in the main chain of the molecule are separated by saturated fluorocarbon groups having 1 to 3 carbon atoms. In addition, two or more fluorocarbon groups may exist in the molecule. A representative structure has a repeating unit represented by the following formula.

[0095] (-CFCF3-CF2-O-) n

[0096] (-CF2-CF2-CF2-O-) n

[0097] (-CF2-CF2-O-) n -(-CF2-O-) m

[0098] (-CF2-CFCF3-O-) n -(-CF2-O-) m

[0099] These structures are described by Kasai in J. Appl. Polymer Sci. 57, 797 (1995). As disclosed in the document, the PFPE acid or its salt may have a carboxylic acid group or its salt at one or both ends. In addition, the PFPE acid or its salt may have a sulfonic acid, phosphonic acid group or its salt at one or both ends. In addition, the PFPE acid or its salt may have different groups at each end. For monofunctional PFPE, the other end of the molecule is usually perfluorinated and may also contain hydrogen or chlorine atoms. The PFPE acid or its salt has at least 2 ether oxygens, preferably at least 4 ether oxygens, and more preferably at least 6 ether oxygens. Preferably, at least one of the fluorocarbon groups separated by the ether oxygen, more preferably at least two of such fluorocarbon groups have 2 or 3 carbon atoms. More preferably, at least 50% of the fluorocarbon groups separated by the ether oxygen have 2 or 3 carbon atoms. In addition, preferably, the PFPE acid or its salt has a total of at least 15 carbon atoms, for example, the preferred minimum value of n or n+m in the repeating unit structure is at least 5. Two or more PFPE acids or salts thereof having an acid group at one or both ends can be used in the production method of the present invention. The PFPE acid or salt thereof preferably has a number average molecular weight of less than 6000 g / mol.

[0100] From the aspect that the modified PTFE can be further high molecular weighted and the stretchability can be improved, the above-mentioned emulsion polymerization is preferably carried out by adding a free radical scavenger or a decomposition agent of a polymerization initiator. The above-mentioned free radical scavenger or the decomposition agent of a polymerization initiator is preferably added after the polymerization reaction starts, preferably before 10% by mass or more, preferably 20% by mass or more of the total TFE consumed in the polymerization reaction is polymerized, and in addition, preferably before 50% by mass or less, preferably 40% by mass or less is polymerized. In the case of performing the pressure relief and re-pressurization described later, it is preferably added afterwards.

[0101] As the free radical scavenger, a compound that is added to the free radical in the polymerization system or has no reinitiation ability after chain transfer is used. Specifically, a compound having the following functions is used: it is easy to undergo a chain transfer reaction with a primary free radical or a growing free radical, and then generate a stable free radical that does not react with the monomer, or it is easy to undergo an addition reaction with a primary free radical or a growing free radical to generate a stable free radical.

[0102] The activity of a substance generally referred to as a chain transfer agent is characterized by a chain transfer constant and a reinitiation efficiency. Among chain transfer agents, a substance having a reinitiation efficiency of substantially 0% is referred to as a free radical scavenger.

[0103] The radical scavenger can be, for example, a compound whose chain transfer constant with TFE at the polymerization temperature is greater than the polymerization rate constant and whose reinitiation efficiency is substantially zero%. "Substantially zero% reinitiation efficiency" means that the generated radicals make the radical scavenger a stable radical.

[0104] Preferred are compounds having a chain transfer constant (Cs) with TFE at the polymerization temperature (=chain transfer rate constant (kc) / polymerization rate constant (kp)) greater than 0.1, and the chain transfer constant (Cs) of the above-mentioned compound is more preferably 0.5 or more, further preferably 1.0 or more, further preferably 5.0 or more, and particularly preferably 10 or more.

[0105] The radical scavenger is preferably at least one selected from the group consisting of, for example, aromatic hydroxy compounds, aromatic amines, N,N-diethylhydroxylamine, quinone compounds, terpenes, thiocyanates, and cupric chloride (CuCl 2 ).

[0106] Examples of the aromatic hydroxy compound include unsubstituted phenol, polyphenol, salicylic acid, m-salicylic acid or p-salicylic acid, gallic acid, and naphthol.

[0107] Examples of the unsubstituted phenol include o-nitrophenol, m-nitrophenol, p-nitrophenol, o-aminophenol, m-aminophenol, p-aminophenol, p-nitrosophenol, etc. Examples of the polyphenol include catechol, resorcinol, hydroquinone, pyrogallol, pyrogallol, naphthol resorcinol, etc.

[0108] Examples of the aromatic amines include o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, and benzidine.

[0109] Examples of the quinone compound include o-benzoquinone, m-benzoquinone, p-benzoquinone, 1,4-naphthoquinone, and alizarin.

[0110] Examples of the thiocyanate include ammonium thiocyanate (NH4SCN), potassium thiocyanate (KSCN), and sodium thiocyanate (NaSCN).

[0111] As the radical scavenger, an aromatic hydroxy compound is preferred, an unsubstituted phenol or a polyphenol is more preferred, and hydroquinone is further preferred.

[0112] From the aspect of reducing the standard specific gravity, the amount of the free radical scavenger added is preferably an amount equivalent to 3% to 500% (molar basis) of the polymerization initiator concentration. A more preferred lower limit is 10% (molar basis), and a further preferred upper limit is 400% (molar basis), and a further preferred upper limit is 300% (molar basis).

[0113] As the decomposition agent of the above-mentioned polymerization initiator, any compound capable of decomposing the polymerization initiator used may be used, for example, at least one selected from the group consisting of sulfites, bisulfites, bromates, diimides, diimide salts, oxalic acid, oxalates, copper salts and iron salts is preferred. As sulfites, sodium sulfite and ammonium sulfite can be cited. As copper salts, copper (II) sulfate can be cited, and as iron salts, iron (II) sulfate can be cited.

[0114] From the aspect of reducing the standard specific gravity, the amount of the above-mentioned decomposition agent added is preferably an amount equivalent to 3% to 500% (molar basis) of the initiator concentration. A more preferred lower limit is 10% (molar basis), and a further preferred upper limit is 400% (molar basis), and a further preferred upper limit is 300% (molar basis).

[0115] In the above-mentioned emulsion polymerization, the polymerization temperature and polymerization pressure are appropriately determined according to the type of monomer used, the molecular weight of the target modified PTFE, and the reaction rate. Usually, the polymerization temperature is 5°C to 150°C, preferably above 10°C, more preferably above 30°C, and further preferably above 50°C. In addition, it is more preferably below 120°C, and further preferably below 100°C.

[0116] The polymerization pressure is usually 0.05 MPaG to 10 MPaG. From the perspective of further improving the breaking strength, the polymerization pressure is more preferably 0.3 MPaG or more, and even more preferably 0.5 MPaG or more. In addition, it is more preferably 5.0 MPaG or less, and even more preferably 3.0 MPaG or less.

[0117] In the above-mentioned emulsion polymerization, from the aspect of easily obtaining the above-mentioned various physical properties, it is preferred that the HFP concentration in the gas in the reactor at the beginning of the polymerization (when adding initiator) is set to 0.01 mol% to 3.0 mol%. Furthermore, the HFP concentration in the gas in the reactor at the moment when 40 mass % of all TFE consumed in the polymerization reaction is polymerized is preferably greater than 0 mol% and is below 0.2 mol%. The above-mentioned HFP concentration is preferably maintained until the polymerization reaction ends thereafter. HFP can be put in once before the polymerization starts, or a part can be put in before the polymerization starts, and added continuously or intermittently after the polymerization starts. By making HFP remain at the end of the polymerization reaction, although the fracture strength of the obtained modified PTFE is increased, the extrusion pressure is reduced.

[0118] In the emulsion polymerization, from the viewpoint of further improving the breaking strength, it is preferred to release the pressure before 5% to 40% by mass of all TFE consumed in the polymerization reaction is polymerized, and then to increase the pressure again by passing only TFE.

[0119] The pressure reduction is preferably performed so that the pressure in the reactor becomes 0.2 MPaG or less, more preferably 0.1 MPaG or less, and further preferably 0.05 MPaG or less. It is also preferably performed so that the pressure becomes 0.0 MPaG or more.

[0120] The above-mentioned depressurization and re-pressurization may be performed multiple times. Depressurization may be performed to a reduced pressure using a vacuum pump.

[0121] The production method may include a step of precipitating the aqueous dispersion to obtain a wet powder of the modified PTFE. The precipitation may be performed by a known method.

[0122] The manufacturing method may include a step of drying the wet powder. The drying is usually carried out by vacuum, high frequency, hot air or the like while keeping the wet powder in a state that is not too fluid, preferably in a static state. Friction between powders, especially at high temperatures, usually has an adverse effect on fine powder PTFE. This is because the particles composed of PTFE have the property that they will simply fibrillate even when subjected to a small shear force, thereby losing the state of the originally stable particle structure.

[0123] The drying temperature is preferably 300°C or lower, more preferably 250°C or lower, further preferably 230°C or lower, still more preferably 210°C or lower, still more preferably 190°C or lower, and particularly preferably 170°C or lower, from the perspective of reducing the extrusion pressure. From the perspective of improving the breaking strength, it is preferably 10°C or higher, more preferably 100°C or higher, further preferably 150°C or higher, further more preferably 170°C or higher, further more preferably 190°C or higher, and particularly preferably 210°C or higher. In order to further improve the strength ratio, it is preferably adjusted appropriately within this temperature range.

[0124] The present invention also provides a modified PTFE (hereinafter also referred to as a second modified PTFE) comprising TFE units and HFP units, wherein the amount of the HFP units is less than 0.1% by mass based on all polymerized units.

[0125] The content of the HFP unit in the second modified PTFE is less than 0.1% by mass, preferably 0.05% by mass or less, more preferably 0.02% by mass or less, and even more preferably 0.01% by mass or less, based on all polymerized units.

[0126] The content of the HFP unit may be 0.0001% by mass or more, or 0.001% by mass or more, based on the total polymerized units.

[0127] The content of the TFE units in the second modified PTFE may be 99.0% by mass or more.

[0128] The second modified PTFE may further include polymerized units based on a modifying monomer other than TFE and HFP (other modifying monomer units).

[0129] The other modifying monomers mentioned above are not particularly limited as long as they can be copolymerized with TFE, and examples thereof include hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF]; perhaloolefins such as chlorotrifluoroethylene; perfluoroolefins; perfluorovinyl ether; perfluoroallyl ether; (perfluoroalkyl)ethylene, ethylene, etc.

[0130] The content of the other modified monomer units is preferably less than 0.1% by mass based on the total polymerized units.

[0131] The total amount of the HFP unit and the other modified monomer units is preferably less than 0.1% by mass based on the total polymerized units.

[0132] The breaking strength of the second modified PTFE is preferably 20.0 N or more, more preferably 25.0 N or more, further preferably 28.0 N or more, and still more preferably 30.0 N or more. The higher the breaking strength, the better, and it may be 100.0 N or less, 80.0 N or less, or 50.0 N or less.

[0133] The thermal instability index (TII) of the second modified PTFE is preferably less than 40, more preferably 15 or less, further preferably 10 or less, and particularly preferably less than 5.

[0134] The thermal instability index is preferably -10 or greater, more preferably 0 or greater.

[0135] The extrusion pressure of the second modified PTFE is preferably 20.0 MPa or less, more preferably less than 18.0 MPa, further preferably less than 17.0 MPa, and still more preferably less than 16.0 MPa. The extrusion pressure may be 5.0 MPa or more, or 10.0 MPa or more.

[0136] The strength ratio represented by the breaking strength (N) / extrusion pressure (MPa) of the second modified PTFE is preferably 1.80 N / MPa or more, more preferably 1.85 N / MPa or more, further preferably 1.90 N / MPa or more, further preferably 1.95 N / MPa or more, further preferably 2.00 N / MPa or more. The higher the strength ratio, the better, and it can be 5.00 N / MPa or less, 4.00 N / MPa or less, or 3.00 N / MPa or less.

[0137] The second modified PTFE is preferably stretchable.

[0138] The stress relaxation time of the second modified PTFE is preferably 450 seconds or longer, more preferably 500 seconds or longer, further preferably 550 seconds or longer, and particularly preferably 600 seconds or longer.

[0139] The longer the stress relaxation time is, the better, and it may be 2000 seconds or less, or 1000 seconds or less.

[0140] The standard specific gravity (SSG) of the second modified PTFE is preferably 2.200 or less, more preferably 2.180 or less, further preferably 2.170 or less, still more preferably 2.160 or less, particularly preferably 2.155 or less, and particularly preferably 2.150 or less.

[0141] In addition, the standard specific gravity is preferably 2.130 or more.

[0142] The second modified PTFE may have the same physical properties as those of the first modified PTFE.

[0143] The second modified PTFE can be appropriately produced by the production method described in connection with the first modified PTFE.

[0144] The first and second modified PTFEs are preferably in the form of powders, more preferably fine powders.

[0145] The first and second modified PTFEs can also be provided in the form of aqueous dispersions. An aqueous dispersion containing particles of either the first or second modified PTFE is also a preferred embodiment of the present invention.

[0146] The average primary particle size of the first and second modified PTFEs is preferably 500 nm or less, more preferably 350 nm or less, further preferably 300 nm or less, and particularly preferably 280 nm or less, and is preferably 100 nm or more, more preferably 150 nm or more, further preferably 170 nm or more, and particularly preferably 200 nm or more.

[0147] The above average primary particle size is measured by the following method.

[0148] The modified PTFE aqueous dispersion was diluted with water until the solid content concentration reached 0.15% by mass, and the transmittance of the projected light at 550 nm relative to the unit length of the obtained diluted emulsion was measured, and the number-based length average particle size determined by measuring the directional diameter using a transmission electron microscope photograph was prepared to prepare a calibration curve. Using this calibration curve, the number average particle size was determined from the measured transmittance of the projected light at 550 nm of each sample as the average primary particle size.

[0149] The average aspect ratio of the primary particles of the first and second modified PTFEs may be 2.0 or less, preferably 1.8 or less, more preferably 1.7 or less, further preferably 1.6 or less, further preferably 1.5 or less, further preferably 1.4 or less, particularly preferably 1.3 or less, particularly preferably 1.2 or less, and most preferably 1.1 or less. In addition, the average aspect ratio may be 1.0 or more.

[0150] The average aspect ratio is determined by observing fluororesin powder or an aqueous fluororesin dispersion diluted to a solid content concentration of about 1% by mass using a scanning electron microscope (SEM), performing image processing on 200 or more particles randomly selected, and calculating the average ratio of the major axis to the minor axis.

[0151] The average secondary particle size of the first and second modified PTFE is preferably 100 μm or more, more preferably 200 μm or more, further preferably 300 μm or more, and is preferably 2000 μm or less, more preferably 1000 μm or less, further preferably 800 μm or less, and particularly preferably 700 μm or less.

[0152] The above average secondary particle size is measured in accordance with JIS K6891.

[0153] The first and second modified PTFEs are particularly useful as raw materials for elongated bodies. The present invention also provides elongated bodies formed from any one of the first and second modified PTFEs.

[0154] The stretched product of the present invention can be obtained by stretching the first or second modified PTFE.

[0155] The stretched body is also preferably in the shape of a film, a tube, a fiber, or a rod.

[0156] When the stretched body is a film (stretched film or porous film), it can be stretched by a known PTFE stretching method.

[0157] Preferably, a sheet-shaped or rod-shaped paste extrudate is roll-stretched in the extrusion direction to obtain a uniaxially stretched film.

[0158] Furthermore, by stretching in the width direction using a tenter or the like, a biaxially stretched film can also be obtained.

[0159] It is also preferred to perform a semi-firing treatment before stretching.

[0160] The stretched body can be made into a porous body with high porosity, and can be suitably used as a filter material for various microfiltration filters such as air filters and reagent filters, a supporting material for polymer electrolyte membranes, and the like.

[0161] Furthermore, it is also useful as a material for products used in the fields of fibers, medicine, electrochemistry, sealing materials, air filtration, ventilation / internal pressure regulation, liquid filtration, and general consumables.

[0162] Specific uses are exemplified below.

[0163] Electrochemical field

[0164] Dielectric material prepreg, EMI shielding material, heat transfer material, etc. More specifically, printed circuit board, electromagnetic shielding material, insulating heat transfer material, insulating material, etc.

[0165] Sealing material field

[0166] Gaskets, sealing pads, pump diaphragms, pump tubes, sealing materials for aircraft, etc.

[0167] Air filtration field

[0168] ULPA filter (for semiconductor manufacturing), HEPA filter (for hospital and semiconductor manufacturing), cylindrical cartridge filter (for industrial use), bag filter (for industrial use), heat-resistant bag filter (for exhaust gas treatment), heat-resistant pleated filter (for exhaust gas treatment), SINBRAN filter (for industrial use), catalytic filter (for exhaust gas treatment), filter with adsorbent (for HDD assembly), ventilation filter with adsorbent (for HDD assembly), ventilation filter (for HDD assembly, etc.), filter for vacuum cleaner (for vacuum cleaner), general-purpose multilayer felt, cartridge filter for GT (for GT interchangeable parts), cooling filter (for electronic equipment housing), etc.

[0169] Ventilation / internal pressure adjustment area

[0170] Freeze-drying materials such as freeze-drying containers, automotive ventilation materials suitable for electronic circuits or lamps, container uses such as container covers, protective ventilation uses for electronic devices including small terminals such as tablet terminals and mobile phone terminals, medical ventilation uses, etc.

[0171] Liquid filtration field

[0172] Semiconductor liquid filters (for semiconductor manufacturing), hydrophilic PTFE filters (for semiconductor manufacturing), filters suitable for chemicals (for reagent processing), filters for pure water production lines (for pure water production), backwash type liquid filtration filters (for industrial wastewater treatment), etc.

[0173] General consumables field

[0174] Clothing, cable guide tubes (removable wires suitable for motorcycles), motorcycle clothing, cast pads (medical protective gear), vacuum cleaner filters, bagpipes (musical instruments), cables (signal cables for guitars, etc.), strings (for stringed instruments), etc.

[0175] Fiber field

[0176] PTFE fiber (fibrous material), sewing thread (fabric), knitting thread (fabric), rope, etc.

[0177] Medical field

[0178] Embedded products (stretchable products), artificial blood vessels, catheters, general surgery (tissue reinforcement materials), head and neck products (dura mater substitutes), oral health (tissue regeneration medicine), plastic surgery (bandages), etc.

[0179] The first and second modified PTFEs can also be suitably used for various additives such as dustproof additives, drip-proof agents, adhesives for batteries, coating applications, and glass cloth impregnation applications.

[0180] Although the embodiments have been described above, it should be understood that various changes may be made to the embodiments and details without departing from the spirit and scope of the claims.

[0181] Example

[0182] Next, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0183] Various physical properties were measured by the following methods.

[0184] Content of modified monomer units

[0185] PTFE powder 19 In the F-NMR measurement, the signal derived from the obtained functional group was calculated based on the following formula.

[0186] HFP content (mass %) = (50A / (50A+25B)) × 100

[0187] (A: integrated value of CF3 signal appearing near -65ppm, B: integrated value of CF2 signal appearing near -120ppm)

[0188] As the chemical shift value, the value used was the value obtained when the peak top of the CF2 signal derived from the polymer main chain was set to -120 ppm.

[0189] Standard Specific Gravity (SSG)

[0190] The measurement was performed by the water displacement method according to ASTM D 792 using a sample formed according to ASTM D 4895.

[0191] Average primary particle size

[0192] The modified PTFE aqueous dispersion was diluted with water until the solid content concentration reached 0.15% by mass, and the transmittance of the projected light at 550 nm relative to the unit length of the obtained diluted emulsion was measured, and the number-based length average particle size determined by measuring the directional diameter using a transmission electron microscope photograph was prepared to prepare a calibration curve. Using this calibration curve, the number average particle size was determined from the measured transmittance of the projected light at 550 nm of each sample as the average primary particle size.

[0193] Average aspect ratio

[0194] An aqueous fluororesin dispersion diluted to a solid content concentration of about 1 mass % was observed using a scanning electron microscope (SEM), and 200 or more particles randomly selected were subjected to image processing, and the average ratio of the major axis to the minor axis was obtained.

[0195] Extrusion pressure

[0196] 21.7 g of lubricant (trade name: Isopar H (registered trademark), manufactured by Exxon) was added to 100 g of modified PTFE powder, and mixed at room temperature for 3 minutes to obtain a PTFE fine powder mixture. Next, the obtained PTFE fine powder mixture was placed at room temperature (25°C) for at least 1 hour before extrusion, and then paste extruded through a hole (diameter 2.5 mm, land length 11 mm, introduction angle 30°) at room temperature with a reduction ratio of 100:1 (ratio of the cross-sectional area of ​​the inlet of the die to the cross-sectional area of ​​the outlet) to obtain a uniform beading (extruded molded body). The extrusion speed, i.e., the punch speed, was set to 20 inches / minute (51 cm / minute). The extrusion pressure is a value obtained by measuring the load when the extrusion load reaches a balanced state in the paste extrusion and dividing it by the cross-sectional area of ​​the barrel used in the paste extrusion.

[0197] Tensile test

[0198] The strips extruded from the paste are heated at 230°C for 30 minutes to remove the lubricant from the strips. Next, the strips (extruded molded bodies) are cut into appropriate lengths, each end is fixed to the chucks at intervals of 2.0 inches (51 mm) between the chucks, and heated to 300°C in an air circulating oven. Next, the chucks are separated at the desired speed (stretching speed) to a separation distance corresponding to the desired stretching (total stretching), and a stretching test is performed. This stretching method is essentially in accordance with the method disclosed in the specification of U.S. Patent No. 4,576,869, except that the extrusion speed (51 cm / min instead of 84 cm / min) is different. "Stretching" refers to the increase in length caused by extension, and is usually expressed in relation to the original length. In the above-mentioned production method, the above-mentioned stretching speed is 100% / sec, and the above-mentioned total stretching is 2400%.

[0199] Breaking strength

[0200] The tensile bar obtained in the above tensile test (made by stretching a bar) was clamped and fixed in movable jaws with a gauge length of 5.0 cm, and a tensile test was performed at 25°C and a speed of 300 mm / min. The strength at break was measured as the breaking strength.

[0201] Thermal Instability Index (TII)

[0202] Measured according to ASTM D 4895.

[0203] Stress relaxation time

[0204] The two ends of the tensile strip obtained in the same manner as the above tensile evaluation test were connected to a fixture to prepare a tensed strip sample with a total length of 8 inches (20 cm), except that the clamp interval was 1.5 inches (38 mm) and the tensile speed was 1000% / second. The oven was maintained at 390°C, and the fixture was inserted into the oven through a slit located in the side of the oven (covered). The time required from the time of insertion into the oven to the breaking of the strip sample was measured as the stress relaxation time.

[0205] Synthesis example 1

[0206] A white solid A was obtained by the method described in Synthesis Example 1 of International Publication No. 2021 / 045228.

[0207] Example 1

[0208] 3580 g of deionized water, 100 g of paraffin wax and 5.4 g of white solid A were added to a 6 liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature regulating jacket, and the autoclave was replaced with nitrogen to remove oxygen while being heated to 70°C. After 0.06 g of HFP was pressed into the autoclave with TFE, TFE was pressed into the autoclave so that the pressure in the system was 0.78 MPaG, and the temperature in the system was maintained at 70°C under stirring. Next, an aqueous solution of 15.4 mg of ammonium persulfate dissolved in 20 g of water was pressed into the autoclave with TFE to start the polymerization reaction. As the polymerization reaction proceeded, the pressure in the system decreased, but TFE was added to maintain the temperature in the system at 70°C and the pressure in the system at 0.78 MPaG.

[0209] When 430 g of TFE was consumed from the start of polymerization, an aqueous solution prepared by dissolving 18.0 mg of hydroquinone as a free radical scavenger in 20 g of water was pressed into the system with TFE. The polymerization was continued thereafter. When the amount of TFE polymerized reached 1540 g from the start of polymerization, stirring and supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, thereby terminating the polymerization reaction. The aqueous dispersion was taken out, cooled, and paraffin was separated to obtain an aqueous PTFE dispersion. The average aspect ratio was 1.40.

[0210] The obtained PTFE aqueous dispersion was diluted to a solid content concentration of 13% by mass, and the PTFE was coagulated under stirring in a container, and then filtered with water to obtain a PTFE wet powder.

[0211] The obtained PTFE wet powder was dried in a hot air circulation dryer set at 180° C. for 18 hours to obtain modified PTFE fine powder.

[0212] The various physical properties of the modified PTFE fine powder obtained were measured. The results are shown in Table 1.

[0213] Example 2

[0214] A PTFE aqueous dispersion and modified PTFE fine powder were obtained in the same manner as in Example 1 except that the drying temperature was changed to 160°C.

[0215] The various physical properties of the modified PTFE fine powder obtained were measured. The results are shown in Table 1.

[0216] Example 3

[0217] A PTFE aqueous dispersion and modified PTFE fine powder were obtained in the same manner as in Example 1 except that the amount of HFP charged was changed to 0.11 g. The average aspect ratio was 1.38.

[0218] The various physical properties of the modified PTFE fine powder obtained were measured. The results are shown in Table 1.

[0219] Example 4

[0220] A PTFE aqueous dispersion and modified PTFE fine powder were obtained in the same manner as in Example 3 except that the addition time of hydroquinone was set to the time when 310 g of TFE was consumed and the supply of TFE was stopped when the polymerization amount of TFE reached 1250 g. The average aspect ratio was 1.35.

[0221] The various physical properties of the modified PTFE fine powder obtained were measured. The results are shown in Table 1.

[0222] Example 5

[0223] A PTFE aqueous dispersion and modified PTFE fine powder were obtained in the same manner as in Example 1 except that the amount of HFP charged was changed to 0.50 g. The average aspect ratio was 1.25.

[0224] The various physical properties of the modified PTFE fine powder obtained were measured. The results are shown in Table 1.

[0225] Example 6

[0226] When 180 g of TFE was consumed from the start of polymerization, the stirring and supply of TFE were stopped, and then the gas in the reactor was slowly released until the pressure of the reactor reached 0.02 MPaG, and then TFE was supplied until the pressure of the reactor reached 0.78 MPaG, and stirring was restarted. Except for the above changes, a PTFE aqueous dispersion and a modified PTFE fine powder were obtained in the same manner as in Example 5. The average aspect ratio was 1.34.

[0227] The various physical properties of the modified PTFE fine powder obtained were measured. The results are shown in Table 1.

[0228] Example 7

[0229] 3580g of deionized water, 180g of paraffin wax, 5.4g of white solid A, and 0.027g of oxalic acid were added to a polymerization kettle with a content of 6 liters equipped with a stainless steel stirring blade and a temperature regulating jacket. The polymerization kettle was replaced with nitrogen to remove oxygen while being heated to 70°C. After the temperature in the kettle was maintained at 70°C under stirring, 1.88g of HFP was added, and TFE gas was introduced to set the pressure to 2.7MPaG. While stirring the contents, an aqueous solution of potassium permanganate in which 3.4mg of potassium permanganate was dissolved in deionized water was added as an initiator to start the polymerization reaction. The aqueous solution of potassium permanganate was continuously added at a certain speed, and TFE was continuously supplied to keep the pressure in the polymerization kettle constant at 2.7MPaG. At the moment when the TFE consumption was 530g, the total amount of deionized water dissolved with the above-mentioned 3.4mg of potassium permanganate was added. At the moment when the TFE consumption was 1440g, the stirring and TFE supply were stopped, and the TFE in the polymerization kettle was purged to end the polymerization reaction. The aqueous dispersion was taken out, cooled, and then the paraffin was separated to obtain a PTFE aqueous dispersion.

[0230] The obtained PTFE aqueous dispersion was diluted to a solid content concentration of 13% by mass, and the PTFE was coagulated under stirring in a container, and then filtered with water to obtain a PTFE wet powder having an average aspect ratio of 1.28.

[0231] The obtained PTFE wet powder was dried in a hot air circulation dryer set at 160° C. for 18 hours to obtain a modified PTFE fine powder.

[0232] The various physical properties of the modified PTFE fine powder obtained were measured. The results are shown in Table 1.

[0233] Example 8

[0234] 3550 g of deionized water, 180 g of paraffin wax and 5.4 g of white solid A were added to a 6-liter polymerization kettle equipped with a stainless steel stirring blade and a temperature regulating jacket. The inside of the polymerization kettle was replaced with nitrogen to remove oxygen while being heated to 80°C. After the temperature in the kettle was maintained at 80°C under stirring, 1.80 g of HFP was added, and TFE gas was introduced to set the pressure to 2.7 MPaG. Then, an aqueous solution of 7.2 mg of ammonium persulfate dissolved in 20 g of water was pressed into TFE to start the polymerization reaction. After the polymerization started, at the moment when 180 g of TFE was consumed, the stirring and supply of TFE were stopped, and then the gas in the reactor was slowly released until the pressure of the reactor reached 0.02 MPaG. Then, TFE was supplied until the pressure of the reactor reached 2.7 MPaG, and stirring was started again. When 410 g of TFE was consumed from the start of polymerization, deionized water in which 11.0 mg of hydroquinone as a free radical scavenger was dissolved was continuously supplied at a certain speed. When the TFE consumption reached 1000 g, the total amount of deionized water in which 11.0 mg of hydroquinone was dissolved was added. When the TFE consumption reached 1440 g, stirring and TFE supply were stopped, and the TFE in the polymerization reactor was purged to terminate the polymerization reaction. The aqueous dispersion was taken out, cooled, and paraffin was separated to obtain a PTFE aqueous dispersion. The average aspect ratio was 1.31.

[0235] The obtained PTFE aqueous dispersion was diluted to a solid content concentration of 13% by mass, and the PTFE was coagulated under stirring in a container, and then filtered with water to obtain a PTFE wet powder.

[0236] The obtained PTFE wet powder was dried in a hot air circulation dryer set at 160° C. for 18 hours to obtain a modified PTFE fine powder.

[0237] The various physical properties of the modified PTFE fine powder obtained were measured. The results are shown in Table 1.

[0238] Comparative Example 1

[0239] PTFE fine powder was obtained in the same manner as in Example 1 except that HFP was not added.

[0240] The various physical properties of the modified PTFE fine powder obtained were measured. The results are shown in Table 1.

[0241] [Table 1]

[0242]

Claims

1. A modified polytetrafluoroethylene comprising tetrafluoroethylene units and hexafluoropropylene units, wherein the amount of the hexafluoropropylene units is 1.0% by mass or less relative to the total polymerized units, The modified polytetrafluoroethylene has a breaking strength of more than 20.0N and a thermal instability index of less than 40.

2. The modified polytetrafluoroethylene according to claim 1, wherein The strength ratio represented by breaking strength (N) / extrusion pressure (MPa) is 1.80 N / MPa or more.

3. The modified polytetrafluoroethylene according to claim 1 or 2, wherein: The stress relaxation time is 500 seconds or more.

4. The modified polytetrafluoroethylene according to any one of claims 1 to 3, wherein The extrusion pressure is less than 17.0MPa.

5. The modified polytetrafluoroethylene according to any one of claims 1 to 4, wherein The extrusion pressure is less than 16.0MPa.

6. A modified polytetrafluoroethylene comprising tetrafluoroethylene units and hexafluoropropylene units, wherein the amount of the hexafluoropropylene units is less than 0.1% by mass based on all polymerized units.

7. The modified polytetrafluoroethylene according to any one of claims 1 to 6, which is in the form of powder.

8. The modified polytetrafluoroethylene according to any one of claims 1 to 7, which is in the form of fine powder. 9 . A stretched body comprising the modified polytetrafluoroethylene according to claim 1 .

Citation Information

Patent Citations

  • Modified polytetrafluoroethylene fine powder and uniaxially oriented porous body

    JP2015127411A

  • Tetrafluoroethylene fine powder and preparation thereof

    US4576869A

  • Aqueous polytetrafluoroethylene emulsion and process for production thereof, aqueous polytetrafluoroethylene dispersion obtained using the emulsion, polytetrafluoroethylene fine powder, and stretch-expanded body

    WO2011055824A1

  • Polytetrafluoroethylene and stretched body

    WO2020022355A1